As a Strategy to Boost Tourism in the Philippines During the New Normal - Jammes Emmanuel; Rex Jhon Bawang; Umidbek Axunov (Multidisciplinary Journal of Tourism, Hospitality, Sport and Physical Education, 2025)
Purpose of the study: This study aims to assess the potential of E-sports as a new approach to promote tourism in the Philippines during the new normal, particularly by exploring how virtual engagement through gaming can contribute to revitalizing the tourism industry. Methodology: The study utilized a quantitative research design using crowdsourcing and snowball sampling. A self-validated survey questionnaire was distributed via Google Forms to members of E-sport communities worldwide, focusing on DOTA2 and Mobile Legends players. Data analysis involved frequency counts, percentages, ranking, mean, t-test, and F-test using Microsoft Excel software. Main Findings: Most respondents were aged 21–25, predominantly male, and from Southeast Asia. DOTA2 was the most popular game. Respondents showed a high level of agreement that E-sports can effectively promote Philippine tourism. There were significant differences in perception based on age, but no significant differences based on gender, nationality, or preferred E-sport. Novelty/Originality of this study: This study introduces E-sports as an emerging strategic tool for tourism promotion in the post-pandemic era. By analyzing global gamer perceptions, it expands the scope of digital tourism initiatives and proposes integrating virtual sports with national tourism strategies—an area that remains underexplored in existing literature.